2014
DOI: 10.3324/haematol.2013.098103
|View full text |Cite
|
Sign up to set email alerts
|

p53 protein expression independently predicts outcome in patients with lower-risk myelodysplastic syndromes with del(5q)

Abstract: © F e r r a t a S t o r t i F o u n d a t i o nchemistry (IHC) has been used as a surrogate marker for TP53 gene mutations in hematologic and other malignancies, including large B-cell lymphoma. [22][23][24] Recently, it was demonstrated that p53 nuclear expression correlated with hemizygous TP53 mutation and outcomes in relapsed myeloma patients treated with lenalidomide. 25 AML following MDS has a dismal prognosis, which makes prediction essential, especially in patients who potentially could be cured by ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
115
2
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(131 citation statements)
references
References 44 publications
(62 reference statements)
9
115
2
5
Order By: Relevance
“…In patients with low-risk myelodysplastic syndrome with del(5q), it was also shown that the presence of Z1% p53-expressing cells was positively correlated with TP53 mutations. 13,22 We also found an excellent correlation betweenZ1% p53 3 þ cells and the presence of TP53 mutation in the 71 cases subjected to sequencing in our study: 29/33 cases (88%) with TP53 mutation were scored as p53 immunohistochemistry-positive. The four falsenegative cases included two cases with a nonsense mutation truncating the protein, likely explaining the loss of detection by immunohistochemistry.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…In patients with low-risk myelodysplastic syndrome with del(5q), it was also shown that the presence of Z1% p53-expressing cells was positively correlated with TP53 mutations. 13,22 We also found an excellent correlation betweenZ1% p53 3 þ cells and the presence of TP53 mutation in the 71 cases subjected to sequencing in our study: 29/33 cases (88%) with TP53 mutation were scored as p53 immunohistochemistry-positive. The four falsenegative cases included two cases with a nonsense mutation truncating the protein, likely explaining the loss of detection by immunohistochemistry.…”
Section: Discussionsupporting
confidence: 73%
“…4,13,15,21,22 To our knowledge, the current study is the first to p53 Expression in therapy-related myeloid neoplasms examine p53 protein expression in a large series of therapy-related myeloid neoplasms. We scored p53 by manual counting and found that, using a cutoff similar to that used in low-risk myelodysplastic syndrome (Z1% 3 þ cells), 22 positivity for p53 was strongly associated with poor outcome in therapy-related myeloid neoplasms. This adverse association was independent of other factors known to influence prognosis, such as age, acute myeloid leukemia vs myelodysplastic syndrome, karyotype risk group, and treatment with stem-cell transplantation.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations